Psephenops panamaensis sp. nov. (Coleoptera: Byrrhoidea: Psephenidae) from Panama - Arce-Pérez, Roberto; Novelo-Gutiérrez, Rodolfo; Cornejo, Aydeé (Zootaxa, 2015)
To date, the genus Psephenops Grouvelle (= Xexanchorinus) is comprised of ten described species with an apparent fragmentary distribution: P. smithi Grouvelle (Antillean, with two subspecies (Bameul 2001)); P. grouvellei Champion (Guatemala); P. haitianus Darlington (Haiti); P. maculicollis Darlington (Costa Rica and Colombia); P. argentinensis Delève (Argentina); P. prestonae Spangler (Costa Rica); P. lupita Arce-Pérez and P. mexicanus Arce-Pérez and Novelo-Gutiérrez (Mexico); P. spiniparameri and P. shepardi Arce-Pérez and Novelo-Gutiérrez (Belize) (Arce-Pérez & Novelo-Gutiérrez 2013). We now extend the number of species known to eleven with the description of a new species from Panama, and the first record of the subfamily Psepheninae for this Central American country (Arce-Pérez & Shepard 2001).